Out of the active site binding pocket for carbonic anhydrase inhibitors. Issue 2 (13th November 2014) - D'Ambrosio, Katia; Carradori, Simone; Monti, Simona M.; Buonanno, Martina; Secci, Daniela; Vullo, Daniela; Supuran, Claudiu T.; De Simone, Giuseppina
Abstract : 2-Benzylsulfinylbenzoic acid binds to human carbonic anhydrase II in a mode completely different from any other class of carbonic anhydrase inhibitors investigated so far. Abstract : A structural study of the adduct which 2-benzylsulfinylbenzoic acid forms with human carbonic anhydrase II is reported, showing a binding mode completely different from any other class of carbonic anhydrase inhibitors investigated so far; this carboxylate binds in a pocket situated out of the enzyme active site.